Transformation of Follicular Lymphoma to Double Hit B-Cell Lymphoma Causing Hypercalcemia in a 69-Year-Old Female: A Case Report and Review of the Literature - Sakshi Kapur; Miles B. Levin (Case Reports in Hematology)
Double hit B-cell lymphomas are rare tumors that are defined by a chromosomal breakpoint affecting the MYC/8q24 locus in combination with another recurrent breakpoint, mainly a t(14;18)(q32;q21) involving BCL2. These tumors mostly occur in adults and carry a very poor prognosis. Double hit lymphomas can occur de novo, or arise from transformation of follicular lymphoma. We report a case of a 69-year-old female with abdominal distention and progressively worsening weakness over six months. Patient presented with severe hypercalcemia and multiple intra-abdominal/pelvic masses. Histopathology results of the abdominal mass were compatible with a double hit B-cell lymphoma. However, bone marrow biopsy results showed a low grade follicular lymphoma, thus suggesting peripheral transformation of follicular lymphoma to double hit B-cell lymphoma. Patient was transferred to a tertiary care center and was started on combination chemotherapy (EPOCH: doxorubicin, etoposide, vincristine, cyclophosphamide, and prednisone). Our paper highlights not only transformation of follicular lymphoma to double hit B-cell lymphoma and the challenges encountered in diagnosing and treating these aggressive tumors, but also the association of new onset/worsening hypercalcemia in such patients.